2012
DOI: 10.1088/0953-8984/24/31/312202
|View full text |Cite
|
Sign up to set email alerts
|

On the magnetic structure of Sr3Ir2O7: an x-ray resonant scattering study

Abstract: Abstract. This report presents azimuthal dependent and polarisation dependent xray resonant magnetic scattering at the Ir L 3 edge for the bilayered iridate compound, Sr 3 Ir 2 O 7 . Two magnetic wave vectors, k 1 =( 1 2 , 1 2 ,0) and k 2 =( 1 2 ,-1 2 ,0), result in domains of two symmetry-related G-type antiferromagnetic structures, noted A and B, respectively. These domains are approximately 0.02 mm 2 and are independent of the thermal history. An understanding of this key aspect of the magnetism is necessar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 20 publications
7
51
0
Order By: Relevance
“…al. reported that both OP-A and -B magnetic setups appear to be consistent with X-ray resonant scattering experiments 15 . Our data confirm that type B is energetically more stable than type A by only 0.1 meV per Ir atom, which is robust upon tested U values between 1 to 3 eV, and as we will show later, also upon epitaxial strain and different types of Ovs.…”
Section: A Bulk Pristine Sr3ir2o7 Casesupporting
confidence: 74%
See 2 more Smart Citations
“…al. reported that both OP-A and -B magnetic setups appear to be consistent with X-ray resonant scattering experiments 15 . Our data confirm that type B is energetically more stable than type A by only 0.1 meV per Ir atom, which is robust upon tested U values between 1 to 3 eV, and as we will show later, also upon epitaxial strain and different types of Ovs.…”
Section: A Bulk Pristine Sr3ir2o7 Casesupporting
confidence: 74%
“…Both experimental measurements and theoretical calculations clearly show that the ground state magnetic structure of Sr 3 Ir 2 O 7 is OP-type 4,5,15 . However, the origin of the experimentally observed unusual magnetic response along the IP direction 25 remains a debated issue that has not been resolved so far.…”
Section: Role Of Oxygen Vacanciesmentioning
confidence: 90%
See 1 more Smart Citation
“…While similar behavior has been reported for Sr 3 Ir 2 O 7 (µ s < 0.04µ B /Ir), 10 recent studies using resonant x-ray scattering have shown that the magnetic structure is a G-type AF 11 with c-axis collinear moments, 12,13 where the spin flop from Sr 2 IrO 4 to Sr 3 Ir 2 O 7 is attributed to the three-dimensional (cubic) character of the J eff = 1/2 ground state that mediates the inter-layer pseudo-dipolar interaction common to the in-plane. 12 However, these compounds exhibit complicated magnetic properties at low temperatures (and under weak magnetic fields) that do not necessarily fit into the current framework of effective theory.…”
supporting
confidence: 77%
“…It has been proposed that the hexagonal iridates Na 2 IrO 3 and Li 2 IrO 3 , which possess layered structures consisting of a honeycomb lattice of Ir 4+ ions, could be experimental realizations of this model. Much of the experimental effort has focused on the attempt to confirm the existence of the J eff = [78,79] determined the magnetic structure of Sr 3 Ir 2 O 7 by REXS and also imaged the magnetic domains, which were found to be of the order of 100 µm. The work of the McMorrow group on the single-layer materials focused on exploring the robustness of the conclusion that these systems are representative of the J eff = 1 2 state, traditionally inferred from the L 2 /L 3 branching ratio for different spin directions and in the presence of significant lattice distortions [80,81].…”
Section: Complex Oxides (A) Iridatesmentioning
confidence: 99%